The System of Economic-Statistical Indicators of the Analysis of Foreign Economic Relations of the Country: A Case Study on Syria - Ahmad, Al Humssi; Zeitoun, Mhd Shaker (European Scientific Journal, ESJ, 2017)
In modern conditions of globalization, the quality of static data of foreign economic relations of the country plays an important role in decision-making about the foreign economic sphere of the country. This is without their quality leading to wrong static analysis of the indicators of foreign economic relations and methods of evaluation. As a result, it is impossible for correct decision not to be made by the government. Also, there are questions about what are the important priorities in the development of foreign economic relations of the country. According to the analysis of static indicators of foreign economic relations of Syria before and during the crisis, we noted that there was a deterioration of all indicators of foreign economic relations due to armed conflict. This includes the increase in the external debt 2.75 times in 2014 compared with the period before the crisis, the decline in exports and imports, and the improvement of egovernment. In addition, work without high-quality cannot control foreign trade transactions.